A Rare Anatomical Finding: Bilateral Accessory Mental Foramen - Zülfikar Karabıyık; Mustafa Kıranatlı (Case Reports in Dentistry)
Aim. Accessory mental foramen (AMF) is a not common anatomical variation. During the surgical procedures involving the mandible such as implant surgery, periapical surgery, jaw surgeries, and periapical surgery and enucleation of pathologies at the mental region, obvious attention should be given to prevent postoperative sequelae. Case Report. Orthopantomograph (OPG) is routinely taken to visualize the maxillofacial region at a dental clinic. OPG shows exactly upper and lower jaw and teeth but superficially reveals some pathology or anatomic variation. It misses sometimes an anatomic landmark such as AMF. As the surgery is planned to a maxillofacial region, a detailed knowledge should be known before going into surgery to not interfere with anatomic landmarks. A 52-year-old male patient was referred to Kütahya Health Science University Dental Hospital, Turkey, to rehabilitate his bilateral partial edentulous lower jaw region. Implant surgery was planned in our patient. OPG was taken to evaluate the maxillofacial region but was unremarkable. Before the implant surgery, CBCT was obtained from our patient. CBCT and a three-dimensional reconstructed model of the male patient showed bilateral accessory mental foramen (AMF). Conclusion. Accessory mental foramen (AMF) carries additional innervation to the chin, mandibular anterior gingiva, and mental region. Reflection and protection of the AMF during the surgery can prevent hemorrhage and neurosensory disturbance at the mental region and can improve quality of life for the patient. CBCT has higher precision but also a higher price and radiation dose. Although anatomical variations are uncommon, they can be found on digital panoramic radiographs but in limited percentage.